Myeloid-Derived Suppressor Cells: A New and Pivotal Player in Colorectal Cancer Progression - Yin, Kai; Xia, Xueli; Rui, Ke; Wang, Tingting; Wang, Shengjun (Frontiers in Oncology, 2020)
Colorectal cancer (CRC) remains a devastating human malignancy with poor prognosis. Of the various factors, immune evasion mechanisms play pivotal roles in CRC progression and impede the effects of cancer therapy. Myeloid-derived suppressor cells (MDSCs) constitute an immature population of myeloid cells that are typical during tumor progression. These cells have the ability to induce strong immunosuppressive effects within the tumor microenvironment (TME) and promote CRC development. Indeed, MDSCs have been shown to accumulate in both tumor-bearing mice and CRC patients, and may therefore become an obstacle for cancer immunotherapy. Consequently, numerous studies have focused on the characterization of MDSCs and their immunosuppressive capacity, as well as developing novel approaches to suppress MDSCs function with different approaches. Current therapeutic strategies that target MDSCs in CRC include inhibition of their recruitment and alteration of their function, alone or in combination with other therapies including chemotherapy, radiotherapy and immunotherapy. Herein, we summarize the recent roles and mechanisms of MDSCs in CRC progression. In addition, a brief review of MDSC-targeting approaches for potential CRC therapy is presented.